2019
DOI: 10.1177/0146621619835501
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Local Independence Assumption of the Rasch Model WithQ3-Based Nonparametric Model Tests

Abstract: Local independence is a central assumption of commonly used item response theory models. Violations of this assumption are usually tested using test statistics based on item pairs. This study presents two quasi-exact tests based on the [Formula: see text] statistic for testing the hypothesis of local independence in the Rasch model. The proposed tests do not require the estimation of item parameters and can also be applied to small data sets. The authors evaluate the tests with three simulation studies. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…This limited performance of the item is not new because, in a sample of the general Italian population, covariance was observed item 1 ("I am more afraid of coronavirus-19") and item 5 ("When I see news and stories about coronavirus-19 on social networks, I get nervous or anxious"; Soraci et al, 2020). This finding suggests an item with local dependence that could compromise the scale's reliability (Christensen et al, 2017;Debelak & Koller, 2020). Along the same lines, a study in Saudi Arabia (Alyami et al, 2020) found a significant error covariance for items 1 and 2 ("My hands get wet when I think about COVID-19").…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This limited performance of the item is not new because, in a sample of the general Italian population, covariance was observed item 1 ("I am more afraid of coronavirus-19") and item 5 ("When I see news and stories about coronavirus-19 on social networks, I get nervous or anxious"; Soraci et al, 2020). This finding suggests an item with local dependence that could compromise the scale's reliability (Christensen et al, 2017;Debelak & Koller, 2020). Along the same lines, a study in Saudi Arabia (Alyami et al, 2020) found a significant error covariance for items 1 and 2 ("My hands get wet when I think about COVID-19").…”
Section: Discussionmentioning
confidence: 98%
“…Thus, a 6-item scale (Fear COVID-6) was obtained. This consideration is significant since local dependency assumption violations can inflate reliability estimators and generate other construct validity problems (Debelak & Koller, 2020).…”
Section: Fear Of Covid-19mentioning
confidence: 99%
“…A post hoc analysis was run using Scheffe's test (MacDonald & Gardner, 2000). As Debelak and Koller (2019) state, several requirements must be fulfilled before using parametric methods in a study. To this purpose, a Kolmogorov-Smirnoff test was conducted using the pretest scores to ensure that students' scores followed a normal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a Rasch analysis, different indicators of the quality of the measurement are evaluated. A first step is checking the internal construct validity, through the exam of some general assumptions concerning the item response theory models [40][41][42], i.e., monotonicity [43,44], local independence [45][46][47], unidimensionality [48,49], and absence of differential item functioning (DIF) or item bias [50,51]. The DIF is related to another key assumption of the Rasch model, relating to the fact that the item parameter estimates should not depend on the person sample, and vice versa.…”
Section: Measurement Of Well-being At Schoolmentioning
confidence: 99%